Draft Annual Plan 1994-95 Government of Madhya Pradesh - Planning Commission (Planning Commission, 1994)
Various employment generation schemes, both for wage employment and self-employment, are proposed to be implemented in the State. Besides, employment is also proposed to be generated indirectly through growth of specific sectors. Special fillip is proposed to be given to the Jawahar Rozgar Yojana by providing Rs. 129.50 crore in the 1994-95 Plan, which is significantly higher by 115.8 percent over the current year's outlay. Similarly, the outlay for the Integrated Rural Development Programme is proposed to be stepped up to Rs. 50.00 crore during the same period.
Government of Madhya Pradesh, Planning, Economics and Statistics Department